Fool's Gold? The Value of Business Awards to Small Businesses. (May 2014) - Jones, Paul; Scherle, Joanne; Pickernell, David; Packham, Gary; Skinner, Heather; Peisl, Tom
This study explores the value and impact that small and medium-sized enterprises (SMEs) derive from winning business awards. Value and impact are explored in terms of enhanced profitability and performance, network development, enterprise profile and brand identity. This study employs a case study methodology with 10 SMEs drawn from a major business awards competition. Key staff were interviewed in these SMEs to explore the impact of winning the business award on the internal and external business environments. Additional organizational documentation and evidence were also collected from each SME. The results indicate both short-term and long-term impacts. In the short term, enterprises benefited in terms of enhanced brand identity in their business network and community. This resulted in enhanced sales revenue and enterprise profile. Moreover, internally, winning an award acted as a motivator for enterprise employees, enhancing their productivity and attitudes towards the business. In the longer term, these factors became less apparent, but the majority of respondents continued to exploit their business award for ongoing strategic advantage.